2009
DOI: 10.1002/polb.21754
|View full text |Cite
|
Sign up to set email alerts
|

Effective in situ synthesis and characteristics of polystyrene nanoparticle‐covered multiwall carbon nanotube composite

Abstract: The higher surface area of selectively grown multiwall carbon nanotubes (MWCNTs) and the better proximity of the reactant species in in situ microemulsion polymerization were used to attach the polystyrene (PS) nanoparticles to the outer wall of MWCNTs. Attachment were achieved by replacing surfactant with PS nanoparticles. SEM showed that the MWCNTs and PS nanoparticles were distributed in the composite. High resolution transmission electron microscopy showed successful anchoring of PS nanoparticles to the ou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
20
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 42 publications
2
20
0
Order By: Relevance
“…In our previous work we presented effective in situ synthesis and characteristics of polystyrene nanoparticle covered multiwall carbon nanotube (MWCNT) composite by microemulsion polymerization [20]. This paper reports the use of microemulsion polymerization to functionalize graphene sheets by PS nanoparticles.…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…In our previous work we presented effective in situ synthesis and characteristics of polystyrene nanoparticle covered multiwall carbon nanotube (MWCNT) composite by microemulsion polymerization [20]. This paper reports the use of microemulsion polymerization to functionalize graphene sheets by PS nanoparticles.…”
Section: Introductionmentioning
confidence: 96%
“…This paper reports the use of microemulsion polymerization to functionalize graphene sheets by PS nanoparticles. This polymerization method has some merit over other emulsion methods because it produces thermodynamically stable polymer particles tens of nm in size, and uses the advantage of surfactants through polymerization [20][21][22]. The higher surface area in graphene and in situ microemulsion enhances the anchoring of PS nanoparticles on graphene through p-p interactions.…”
Section: Introductionmentioning
confidence: 98%
“…Figure 7a shows the glass transition temperature (T g ), which defines the pseudosecond-order phase transition. The grafting of PS nanoparticles on the outer wall of the MWCNT resulted in an increase in T g [17]. The T g of the pristine PS nanoparticles and 10 wt% nanocomposite was observed at 968C and 1108C, respectively.…”
Section: Resultsmentioning
confidence: 86%
“…In a previous report, we have shown the attachment of PS nanoparticles to the MWCNTs and graphene, in which we have shown that in the emulsion process, Brownian motion of emulsified monomer droplets and MWCNTs or graphene inside the water causes collisions between these two species, which further provides anchoring sites for the juvenile PS nanoparticles on the MWCNT or graphene surface [17][18][19]. The anchoring of PS to the MWCNT occurred through p-p stacking.…”
Section: Resultsmentioning
confidence: 94%
See 1 more Smart Citation